Cheap talk about the detection probability - Florian Baumann; Tim Friehe (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
This paper analyzes whether the behavior of potential offenders can be guided by information on the actual detection probability transmitted by the policy maker. It is established that, when viewed as a cheap-talk game, the existence of equilibria with information transmission depends on the level of the sanction, the level of costs related to imposing the sanction, and the level of social harm resulting from the offense. In addition, we find that the policy maker (i.e., society as a whole) is not necessarily better off ex ante when more information is transmitted in equilibrium, but that potential offenders always are.
Keywords: K42; H23; C72; 330; crime; cheap talk; law enforcement; imperfect information